Prevalence of Anti Tuberculousis Drug Induced Hepatitis in Patients on Anti Tuberculous Drug in Mardan Medical Complex (Medical Forum Monthly, 2024)
Objective: To determine the frequency of anti tuberculousis drugs induced hepatitis in Mardan Medical Complex.Study Design: Descriptive / cross sectional studyPlace and Duration of Study: This study was conducted at the chest OPD and TB centre of Mardan Medical Complex, Mardan from November 2018 to July 2019.Materials and Methods: Diagnosed 309 cases of TB both pulmonary and extra pulmonary were taken. Among these only category I TB patients were selected and followed up for the development of ATT induced hepatitis.Results: Study included a total of 309 patients in which 170 (55.01%) were male patients and 139 (44.98%) were female patients. Ages of the patients ranged between 15 and 80 years with a mean age of 34.8 years among male while 14 and 80 years with an mean age of 38.40 years among female. Out of 309 patients only 56 (18.12%) patients developed ATT induced hepatitis.Conclusion: ATT induced hepatitis is an important and common side effect of anti tuberculous therapy and needs early recognition and treatment to avoid non compliance to ATT and treatment failure.